In Vitro Comparison of Root Surface Treatment Effect between Root Scaling with Ultrasonic Inserts and Gracey Curette and Polishing with Different Cleaning Pastes - Angelica Bertacci; Daniele Moro; Gianfranco Ulian; Giovanni Valdrè (Applied Sciences, 2021)
The aim of this study was the morphological evaluation of root surfaces subjected to manual (curette) and ultrasonic (conventional and diamond tips) scaling. The surface was then polished with a rubber cup and three medium-sized pastes. Ninety teeth were randomly divided into three groups of 30 and subjected to three different root instrumentation: (1) manual instrumentation with a Gracey® curette; (2) ultrasonic instrumentation with a standard steel tip (Universal Perio S-SERIES: USU, Hu-Friedy, Chicago, IL, USA) at a power equal to 50%; and (3) with a diamond tip (Punta Piezo Serie E Scaling, Hu-Friedy, Chicago, IL, USA) at a power of 20%. Each group of the instrumented teeth was then divided in three subgroups of 10 and subjected to 30 s of rubber polishing with three different polishing pastes with medium grain sizes in single-dose cups: (1) Ultrapro Tx cool mint medium®; (2) Stomyprox media®; and (3) Nupro medium orange®. Polyether root surface replicas were then taken from all 90 samples and analyzed by SEM to evaluate surface morphology after scaling and polishing procedures. All scaling techniques caused an alteration of the root surface without statistically significant difference, whereas polishing resulted in maintenance or improvement of the surface texture.